2021
DOI: 10.1101/2021.09.30.462684
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Powassan Viruses Spread Cell to Cell During Direct Isolation from Ixodes Ticks and Persistently Infect Human Brain Endothelial Cells and Pericytes

Abstract: Powassan viruses (POWVs) are neurovirulent tick-borne flaviviruses emerging in the Northeastern U.S., with a 2% prevalence in Long Island (LI) deer ticks (Ixodes scapularis). POWVs are transmitted during a 15 minutes tick bite, and enter the CNS to cause encephalitis (10% fatal) and long-term neuronal damage. POWV-LI9 and POWV-LI41 present in LI Ixodesticks were isolated by directly inoculating VeroE6 cells with tick homogenates and detecting POWV infected cells by immunoperoxidase staining. Inoculated POWV-LI… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 85 publications
(133 reference statements)
0
8
0
Order By: Relevance
“…In these studies, lethality varied by strain, dose, kinetics, and suggested requirements for tick saliva in directing neurovirulence (29,33) . Our analysis was performed using mice 10-50 weeks of age and POWV LI9, a strain from circulating Ixodes ticks isolated in VeroE6 cells (21,42) . Footpad inoculation of POWV LI9 into 10-50 week old C57BL/6 mice resulted in 82% lethality in 50 week old mice, with lethality sequentially reduced with age to 7.1% in 10 week old mice (Figure 1B,E).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In these studies, lethality varied by strain, dose, kinetics, and suggested requirements for tick saliva in directing neurovirulence (29,33) . Our analysis was performed using mice 10-50 weeks of age and POWV LI9, a strain from circulating Ixodes ticks isolated in VeroE6 cells (21,42) . Footpad inoculation of POWV LI9 into 10-50 week old C57BL/6 mice resulted in 82% lethality in 50 week old mice, with lethality sequentially reduced with age to 7.1% in 10 week old mice (Figure 1B,E).…”
Section: Discussionmentioning
confidence: 99%
“…Like SP, this may reflect LI9 persistence (27) , or result from persistent auto-amplifying inflammatory CNS responses. Whether the use of very young mice or POWV SP (27) , serially passaged in murine brains (25) , account for differences in murine persistence may be revealed using POWV reverse genetics (42) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations